Micro patterning atop shape memory polymers - Liu, Na (2012)
Shape memory polymers (SMP) are a new class of materials that have become popular recently due to its potential applications in fields related to engineering and medicine. Understanding how SMPs behave under different thermal or mechanical conditions will open exciting possibilities. Researchers have shown considerable interest in the thermomechanical properties of SMPs, but the behaviour is not yet fully understood. The thesis details the studies performed in this domain to better understand the thermomechanical properties of SMPs. Interesting effects like “butterfly effect” was observed and the mechanism was studied in detail. The behavior of styrene SMPs on micro and nano indentation is studied to investigate the thermomechanical properties. The study revealed that SMPs are a feasible material for patterning in the micro and nano scale. This provides excellent opportunities to employ SMPs in MEMS/NEMS devices and the applications requiring controllable surface topography. Different patterning techniques were also investigated to demonstrate the possibility of forming the surface topography with various shapes. The results shows good agreement with the numerical simulations performed. The work was extended on Ni powder based SMP composites to study the self assembly property and its applications.